2015
DOI: 10.1200/jco.2015.33.3_suppl.278
|View full text |Cite
|
Sign up to set email alerts
|

Final results of phase Ib of anticancer stem cell antibody tarextumab (OMP-59R5, TRXT, anti-Notch 2/3) in combination with nab-paclitaxel and gemcitabine (Nab-P+Gem) in patients (pts) with untreated metastatic pancreatic cancer (mPC).

Abstract: 278 Background: Tarextumab (TRXT), fully human IgG2 antibody, inhibits signaling Notch 2, 3 receptors. Tumor regression seen in Notch 3 patient-derived PC xenografts when TRXT added to Nab-P+Gem. The maximum tolerated dose (MTD) of single agent TRXT was 7.5mg/kg every other week (Smith, EORTC 2012); the main dose limiting toxicity (DLT) was Grade 3 diarrhea. This study evaluates MTD, pharmacokinetics (PK), pharmacodynamics (PD) and early efficacy of TRXT + Nab-P+Gem in mPC. Methods: Cohorts of 3-6 pts treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Preliminary results from the phase 1B trial demonstrated significant activity of a 15 mg/kg dose of tarextumab combined with standard doses of gemcitabine and nab-paclitaxel. The reported median time of progression-free survival was 5.6 months, and median time of overall survival was 11.6 months; 38% of this patient population had a response to the 3-drug combination, and response rate was even higher in the small number of patients whose tumors expressed high levels of NOTCH3 117 .…”
Section: Genetic Alterations As Therapeutic Targetsmentioning
confidence: 91%
“…Preliminary results from the phase 1B trial demonstrated significant activity of a 15 mg/kg dose of tarextumab combined with standard doses of gemcitabine and nab-paclitaxel. The reported median time of progression-free survival was 5.6 months, and median time of overall survival was 11.6 months; 38% of this patient population had a response to the 3-drug combination, and response rate was even higher in the small number of patients whose tumors expressed high levels of NOTCH3 117 .…”
Section: Genetic Alterations As Therapeutic Targetsmentioning
confidence: 91%
“…In view of the encouraging preclinical findings, early phase trials were initiated in metastatic PDAC and extensive stage small cell lung cancer. Results from both phase Ib clinical trials were potentially promising, with reported response rates of 84% and 74% in the small cell lung and pancreatic cancer trials, respectively . Analysis of the phase Ib clinical trial in PDAC demonstrated a PFS of 5.6 months and OS of 11.6 months in patients treated with tarextumab in combination with gemcitabine and nab‐paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea, fatigue, and anemia were the most common tarextumab‐related toxicities, and the events were mostly Grade 1 or 2. The overall response rate (CR + PR) was 29% . The median PFS and OS were 5.6 and 11.6 months, respectively.…”
Section: Introductionmentioning
confidence: 95%
“…Table 2 outlines current new drug discovery efforts against these key signal transduction pathways [11,47,73,[89][90][91][92][93][94].…”
Section: Molecular Signaling In Cscsmentioning
confidence: 99%